2016
DOI: 10.1371/journal.pone.0166315
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Error Awareness as a Mediator of the Relationship between Subjective Concerns and Cognitive Performance in Older Adults

Abstract: ObjectivesSubjective concerns of cognitive decline (SCD) often manifest in older adults who exhibit objectively normal cognitive functioning. This subjective-objective discrepancy is counter-intuitive when mounting evidence suggests that subjective concerns relate to future clinical progression to Alzheimer’s disease, and so possess the potential to be a sensitive early behavioural marker of disease. In the current study, we aimed to determine whether individual variability in conscious awareness of errors in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
1
5
1
Order By: Relevance
“…Unlike previous research connecting depression to SCC (Buckley, Laming, Chen, Crole, & Hester, 2016), the present study highlights rumination as particularly relevant for SCC. To this end, we also considered symptoms of depression and PTSD, and our data support that the relationships observed here are not due to these constructs alone.…”
Section: Discussioncontrasting
confidence: 93%
“…Unlike previous research connecting depression to SCC (Buckley, Laming, Chen, Crole, & Hester, 2016), the present study highlights rumination as particularly relevant for SCC. To this end, we also considered symptoms of depression and PTSD, and our data support that the relationships observed here are not due to these constructs alone.…”
Section: Discussioncontrasting
confidence: 93%
“…In line with previous research; younger participants, the more educated, and those with fewer depressive symptoms reported less frequent forgetting (e.g., Buckley et al, 2016; Gilewski et al, 1990; Hülür et al, 2014; for an overview, see Hertzog & Pearman, 2014). Notably, the associations between these variables and subjective memory were comparable in magnitude to associations between subjective memory and memory performance.…”
Section: Discussionsupporting
confidence: 87%
“…If subjective memory ratings have discriminant validity for memory performance, subjective memory should be more closely associated with memory performance than with other variables (Hülür & Gerstorf, 2015). So far, such studies of discriminant validity of subjective memory ratings have found that subjective memory ratings are as closely or even more closely associated with variables other than memory, such as depressive symptoms (e.g., Buckley, Laming, Chen, Crole, & Hester, 2016; Crane, Bogner, Brown, & Gallo, 2007; O’Shea et al, 2016), health (Montejo Carrasco, Montenegro-Pena, Lopez-Higes, & Borja, 2016; Rickenbach, Agrigoroaei, & Lachman, 2015) or personality (e.g., Pearman & Storandt, 2005; Steinberg et al, 2013).…”
mentioning
confidence: 99%
“…More recently, the translational utility of metacognitive experimental tasks has become evident in the context of subjective cognitive decline (SCD)—a “pre-clinical” state receiving growing attention as a potential harbinger to the objective cognitive symptoms that occur in mild cognitive impairment and later in dementia (Buckley, Laming, Chen, Crole, & Hester, 2016; Cosentino et al, 2018). SCD is characterized by the subjective perception that one’s cognition has declined prior to objective evidence of such decline on diagnostic testing (Jessen et al, 2014).…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…Determining the integrity of metamemory among individuals with SCD may thus shed important light on its utility as a marker of preclinical AD. Indeed, recent work is attempting to use metamemory frameworks to investigate whether deficits in lower levels of awareness mediate how SCD maps onto objective cognition (Buckley et al, 2016; Cosentino et al, 2018). Results from preliminary studies are mixed, and much work is needed to determine how assessing metacognition and integrating it into the conceptualization of SCD can enhance the utility of this potential biomarker.…”
Section: Directions For Future Researchmentioning
confidence: 99%